Synthesis of 2D NiFe2O4 nanoplates/2D Bi2WO6 nanoflakes heterostructure: An enhanced Z-scheme charge transfer and separation for visible-light-driven photocatalytic degradation of toxic pollutants. Issue 5 (October 2021) - Koutavarapu, Ravindranadh; Tamtam, Mohan Rao; Lee, Sang-Gyenog; Rao, M.C.; Lee, Dong-Yeon; Shim, Jaesool
Abstract: Water pollution is a worldwide concern due to excessive discharge of toxic contaminants to water streams. Effective treatment of organic pollutants in wastewater by utilizing visible-light is a promising method to resolve environmental problems. In the present work, we have demonstrated a facile one-step hydrothermal strategy for the synthesis of a binary NiFe2 O4 /Bi2 WO6 heterostructured nanocomposite. Further, the utility towards photocatalytic degradation of tetracycline (TC) and methylene blue (MB) has been evaluated. The characterization results revealed that the two-dimensional (2D) Bi2 WO6 nanoflakes were inserted upon 2D NiFe2 O4 nanoplates, which enhanced the interfacial contact and improved visible-light absorption efficiency, resulting in excellent photogenerated charges separation and transfer. The NiFe2 O4 /Bi2 WO6 heterostructured nanocomposite exhibited higher TC degradation (96.81%) in 96 min and MB degradation (99.16%) in 60 min than the pure samples and remained stable for four successive cycles. The apparent reaction rate constant ( k ) of 20 mg loading of Bi2 WO6 over NiFe2 O4 (NFBW-20) exhibited the best photocatalytic performance among the all prepared materials, which was 7.15 (TC) and 9.19 (MB) times that of pristine Bi2 WO6, and 6.02 (TC) and 6.41 (MB) times that of pure NiFe2 O4 . Radical trapping experiments confirmed O2 −, and OH radicals were critical active species in the degradation mechanism, which supports the Z-scheme photocatalytic mechanism. Mott–Schottky measurements were used determine the positions of the conduction and valence bands of the samples, and a possible photocatalytic mechanism for TC and MB degradation was proposed according to experimental results. This study offers a novel effective avenue to design efficient binary heterostructured nanocomposites with superior visible-light response for environmental remediations. Graphical Abstract: ga1 Highlights: Hydrothermally prepared Bi2 WO6 nanorods were inserted on NiFe2 O4 nanoplates. The charge-transfer pathway followed a Z-scheme mechanism. The nanocomposite degraded 96.81% of TC and 99.16% of MB under visible-light. Strong interfaces and charge separation improved the performance of 2D/2D heterostructure.